ANALISIS KINERJA RUAS JALAN TAN MALAKA (SEGMEN PASAR DANGUNG – DANGUNG) KABUPATEN LIMA PULUH KOTA - Kholis, Alfin; Yermadona, Helga; Endri, Endri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Dangung-dangung market is located on Jalan Tan Malaka, Limapuluh Kota Regency, which has a heavy traffic volume coupled with high side obstacles due to parking on the road and traders on the shoulder of the road. The aim of this research is to provide alternative suggestions for improving the performance of sections on the Tan Malaka road. From the results of the performance analysis for the performance of road sections in existing conditions, namely, the degree of saturation in existing conditions, precisely on market days, is 0.84 with a service level of